Legal Implications of Euthanasia Practices on the Medical Profession - Samudra, Muhammad Bima; Gunadi, Ariawan (Jurnal Indonesia Sosial Sains, 2025)
Euthanasia is a controversial act that involves the termination of a person's life upon voluntary request to alleviate suffering from a terminal illness. This practice triggers ethical, legal and moral debates, especially in the context of different regulations in various countries. This research aims to analyze legal regulations related to euthanasia in Indonesia and several other countries, as well as identify relevant ethical principles. The research method used is normative method with statutory and conceptual approaches. The research data is obtained through a literature study, which involves an analysis of legal regulations, academic literature, as well as the results of empirical studies. The results showed that in Indonesia, euthanasia is prohibited under Article 344 of the Criminal Code, while in the Netherlands and Belgium, the practice is allowed under strict conditions to protect individual autonomy and ensure ethical implementation. In conclusion, although euthanasia is considered a form of respect for individual rights in some countries, in Indonesia this practice is against the law, religious norms, and culture. This study recommends the development of quality palliative care to reduce patient suffering without having to consider euthanasia, as well as encouraging public discussion on this issue in Indonesia.